International market research : a financial perspective - Hibbert, Edgar P. (Blackwell Business, 1996)
This book is divided into tn chapters: Marketing Research; Planning and Organizing Research; International Research Decisions; Project Finance; Financing the Marketing Programme; Research methods; Information Technology and Research; Application of Research and Financial Appraisal; Research Decisions: the Marketing Mix; Developing Business Plans.